2015
DOI: 10.1016/j.jvs.2014.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Debate: Whether endovascular repair offers a survival advantage over open repair for ruptured abdominal aortic aneurysms

Abstract: During the last decade, new information and reports have been published regularly describing endovascular and open repair of ruptured abdominal aortic aneurysms, but despite this, disagreement persists over which therapy is best. At the root of the problem is the discrepancy between the findings of multiple well-performed observational studies and a smaller number of randomized controlled trials. Our debaters do an excellent job of summarizing the current status of the world literature and describing their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Patient selection, both in terms of haemodynamic and anatomical stability, has an impact on the choice of treatment and, likewise, on the outcome. 25,26 The patients offered EVAR in this cohort were older and sicker, while no data are available regarding anatomical constraints, including neck length, width, or angulation. It is interesting to note however, that OAR patients had larger AAA diameters, which is known to render aortas less amenable to treatment by EVAR, as well as to poorer outcomes overall.…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection, both in terms of haemodynamic and anatomical stability, has an impact on the choice of treatment and, likewise, on the outcome. 25,26 The patients offered EVAR in this cohort were older and sicker, while no data are available regarding anatomical constraints, including neck length, width, or angulation. It is interesting to note however, that OAR patients had larger AAA diameters, which is known to render aortas less amenable to treatment by EVAR, as well as to poorer outcomes overall.…”
Section: Discussionmentioning
confidence: 99%
“…Endoprosthesis placement can serve as a temporary measure, until the patient is hemodynamically stable, postponing the need for open surgery. 45 Some studies have suggested that such bias from patient selection influences the comparison between the procedures, and that the mortality rate for EVAR and open repair for ruptured AAA are really similar. 46 Foster et al compared studies in patients hemodynamically stable who performed a CT scan to confirm the diagnosis of ruptured AAA.…”
Section: Treatmentmentioning
confidence: 99%
“…103 Although EVAR has been shown to significantly reduce postoperative mortality when compared with OSR for elective AAA repair, its benefit over OSR for the treatment of rAAA remains a matter of debate. 104 Observational studies have shown a significant improvement in mortality with EVAR for rAAA (rEVAR) when compared with OSR. [105][106][107][108] A review of rAAA cases in the Nationwide Inpatient Sample over a 10-year period revealed 42,126 cases.…”
Section: Tevar and Strokementioning
confidence: 99%
“…Thus, in these studies, patients who have a higher likelihood of survival by virtue of their clinical and anatomic characteristics are more likely to undergo rEVAR. 104 A number of RCTs have been conducted to address this issue. [110][111][112][113] None of the RCTs has shown a difference in mortality between rEVAR and OSR.…”
Section: Tevar and Strokementioning
confidence: 99%